Relationship Between Serum 25-Hydroxy Vitamin D Level and Menstrual Cycle Irregularity: A Cross-Sectional Study - Uzma Afreen, Mubushra Samina, Shaima Sultana Memon, Hafiz Syed Muhammad Osama Jafri, Sumaira Riffat, Saba Abrar, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The significance of vitamin D deficiency in the progress of menstrual disorders in women is a topic of great interest in studies. Several studies have found that taking an increased vitamin D supplement can help restore the menstrual cycle. Aim: To investigate the relationship between vitamin D and menstrual cycle irregularity. Material and Methods: In this cross-sectional study, serum vitamin D levels were measured in 150 outpatient women with menstrual disorders (n=75), compared to women with comparable profiles (n=75) with symptoms other than menstrual disorders compared. Results: A decreased level of vitamin D was associated with a 13.3 times odds of an irregular cycle (95% CI): p < 0.001). 25-hydroxy vitamin D was not associated with age or body mass index. We found a significant difference (p < 0.001) in mean vitamin D levels among the females with irregular cycles vs. regular cycles Practical implication:There is scarcity of literature on vitamin D and menstrual periods so current study assessed the relationship between vitamin D and menstrual cycle irregularity in womens. Conclusion: Lower 25(OH)D levels are linked to irregular menstrual cycles. Our findings indicate that vitamin D has an effect on the reproductive axis, which has wider scope for reproductive potential. Keywords: Menstrual disturbances, Ovulation, Vitamin D deficiency, polycystic ovarian syndrome.